2010
DOI: 10.1016/j.visres.2010.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Asia has the global advantage: Race and visual attention

Abstract: In studies of visual attention, and related aspects of cognition, race (continent/s of ancestry) of participants is typically not reported, implying that authors consider this variable irrelevant to outcomes. However, there exist several findings of perceptual differences between East Asians and Caucasian Westerners that can be interpreted as relative differences in global versus local distribution of attention. Here, we used Navon figures (e.g., large E made up of small Vs) to provide the first direct compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
143
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 51 publications
6
143
4
Order By: Relevance
“…In a series of studies, it has been consistently demonstrated that WC observers attend to and process more effectively local features, while EA observers exhibit a global attention bias (McKone et al 2010;Nisbett and Miyamoto 2005;Hedden et al 2008;Kitayama et al 2003). For example, Kitayama et al (2003) presented Westerners and Esterners a vertical line within a square frame and subsequently asked the observers to report the length of the line (i.e., rod-and-frame task).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a series of studies, it has been consistently demonstrated that WC observers attend to and process more effectively local features, while EA observers exhibit a global attention bias (McKone et al 2010;Nisbett and Miyamoto 2005;Hedden et al 2008;Kitayama et al 2003). For example, Kitayama et al (2003) presented Westerners and Esterners a vertical line within a square frame and subsequently asked the observers to report the length of the line (i.e., rod-and-frame task).…”
Section: Introductionmentioning
confidence: 99%
“…EA observers are also more distracted by unrelated global information and faster at detecting targets at the global level compared to Westerners (Boduroglu et al 2009;Petrova et al 2013), which suggest they might have a global selective attention bias. Within this framework yet, McKone et al (2010) used Navon stimuli to directly quantify the global/local attention bias between Westerners and Easterners. Navon figures are hierarchical stimuli comprising a large global shape constituted by small local shapes (Navon 1977).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations